Compressive Loads on the Lumbar Spine During Lifting: 4D WATBAK versus Inverse Dynamics Calculations - M. H. Cole; P. N. Grimshaw (Applied Bionics and Biomechanics)
Numerous two- and three-dimensional biomechanical models exist for the purpose of assessing the stresses placed on the lumbar spine during the performance of a manual material handling task. More recently, researchers have utilised their knowledge to develop specific computer-based models that can be applied in an occupational setting; an example of which is 4D WATBAK. The model used by 4D WATBAK bases its predications on static calculations and it is assumed that these static loads reasonably depict the actual dynamic loads acting on the lumbar spine. Consequently, it was the purpose of this research to assess the agreement between the static predictions made by 4D WATBAK and those from a comparable dynamic model. Six individuals were asked to perform a series of five lifting tasks, which ranged from lifting 2.5 kg to 22.5 kg and were designed to replicate the lifting component of the Work Capacity Assessment Test used within Australia. A single perpendicularly placed video camera was used to film each performance in the sagittal plane. The resultant two-dimensional kinematic data were input into the 4D WATBAK software and a dynamic biomechanical model to quantify the compression forces acting at the L4/L5 intervertebral joint. Results of this study indicated that as the mass of the load increased from 2.5 kg to 22.5 kg, the static compression forces calculated by 4D WATBAK became increasingly less than those calculated using the dynamic model (mean difference ranged from 22.0% for 2.5 kg to 42.9% for 22.5 kg). This study suggested that, for research purposes, a validated three-dimensional dynamic model should be employed when a task becomes complex and when a more accurate indication of spinal compression or shear force is required. Additionally, although it is clear that 4D WATBAK is particularly suited to industrial applications, it is suggested that the limitations of such modelling tools be carefully considered when task-risk and employee safety are concerned.